Corruption and travel: effects of China’s anti-graft campaign on Macao - Li, Tao; Sheng, Li (DIE ERDE – Journal of the Geographical Society of Berlin, 2018)
Using differences-in-differences regression models, this research note tries to evaluate the effects of China’s anti-graft campaign on tourism in Macao. It finds that anti-corruption policies significantly curbed gambling with public money in Macao, causing a recent drop in Macao’s gaming revenue. Furthermore, the more strongly the campaigns have been enforced, the less tourists go to the city of Macao. Macao is urged to diversify its casino-dominated and mainland China-dependent economy.